A Network Path Method for Connecting Cross-Seam Using Ground Relay in LEO Satellite Network - Chu, Heon Woo; Moon, Tae Han; Lee, Won Jae; Kim, Jae Hyun (Proceedings - IEEE Consumer Communications and Networking Conference, CCNC, 2025)
This paper proposes a method to overcome the cross-seam in a low Earth orbit (LEO) satellite network. In cross-seam, satellite links cannot be established due to differences in satellite movement directions. The proposed method involves utilizing ground relay to resolve this problem. The Walker-Star constellation has polar regions and cross-seams, where inter-satellite link connection is impossible due to relative velocity. In this paper, we compare the performance results in a satellite network when ground relay is utilized in a cross-seam. We analyze the propagation delay and the number of satellite hops. It analyzes satellite communication performance with and without a ground relay to major cities from Seoul. Also, the maximum performance improvement provided by the ground relay is analyzed. As a result of the analysis, the ground relay reduces propagation delay by up to 76% and reduces satellite hop count by 89%.
Keywords: Cross-seam; Ground relays; Intersatellite links; Low earth orbit satellite network; Low earth orbit satellites; Oneweb; Performance; Propagation delays; Satellite network; Walker-star constellation; cross-seam; ground relay; inter-satellite link; LEO satellite network; OneWeb; propagation delay; Walker-Star constellation